The system of constant current focus klystron KIU-37 master pulsed microwave generator electron linear accelerator - Beloglazov, V.I.; Tur, Yu.D.; Titarenko, Yu.A.; Filippov, A.V.; Romanovsky, S.K. (Вопросы атомной науки и техники, 2015)
In order to ensure long-term stability of beam parameters of linear accelerators is working on stabilizing the excitation of high-power systems. At this stage the solution of the problem, developed and applied in practice stabilization focusing coil current klystron KIU-37 to eliminate the dependence of the output power from the mains supply voltage fluctuations and other destabilizing factors. Its use has provided the stability of the output current in the range of ±0.5% with changes in the supply voltage ±10%, which, in turn, made it possible to significantly increase the long term stability of parameters of the excitation signal. З метою забезпечення довготривалої стабільності параметрів пучків лінійних прискорювачів проводяться роботи по стабілізації збудження систем високочастотного живлення. На цьому етапі рішення поставленої задачі, розроблена і застосована на практиці система стабілізації струму фокусуючої котушки клістрона КИУ-37 з метою усунення залежності вихідної потужності від коливань напруги живлячої мережі і інших дестабілізуючих чинників. Її використання забезпечило стабільність вихідного струму в межах +0,5% при змінах напруги живлячої мережі +10%. С целью обеспечения долговременной стабильности параметров пучков линейных ускорителей проводятся работы по стабилизации возбуждения систем высокочастотного питания. На этом этапе решения поставленной задачи разработана и применена на практике система стабилизации тока фокусирующей катушки клистрона КИУ-37 с целью устранения зависимости выходной мощности от колебаний напряжения питающей сети и других дестабилизирующих факторов. Ее использование обеспечило стабильность выходного тока в пределах +0,5% при изменениях напряжения питающей сети +10%.